2009
DOI: 10.3109/03639040903025863
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced APAP de-agglomeration

Abstract: This article presents a useful method for formulation and process development. Exposing blends to higher shear rates and especially to strain mitigates APAP agglomeration in blends. Finer APAP presents more agglomerates and the type of excipient used affects the degree of APAP agglomeration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…About the effects of process conditions, the authors found that the abrasion rate increased with the increase of the rotation speed, the mixer size, and the filler particle size. The effects of the mixer rotation speed and the mixer size on abrasion were consistent with experiments . In addition, it was found that the Stoke number, defined as the ratio between the kinetic energy density of a powder bed and work of fracture of an agglomerate, was proportional to the abrasion rate, as observed in the experiments …”
Section: Introductionsupporting
confidence: 83%
“…About the effects of process conditions, the authors found that the abrasion rate increased with the increase of the rotation speed, the mixer size, and the filler particle size. The effects of the mixer rotation speed and the mixer size on abrasion were consistent with experiments . In addition, it was found that the Stoke number, defined as the ratio between the kinetic energy density of a powder bed and work of fracture of an agglomerate, was proportional to the abrasion rate, as observed in the experiments …”
Section: Introductionsupporting
confidence: 83%
“…27 Broad bands are obtained at no shear conditions. As the strain is increased the bands became more defined as observed in Figs 3a to c. These spectra show significant differences in two spectral regions: 7450-7000 cm À1 and 5600-5100 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The shear treatment de-agglomerates the constituent powder, reducing the average size of microparticles. 27 As a result, this treatment reduces the scattering intensity. Thus, 160 revolutions (Figure 9b) increase the tilt of BSDF (θ), and after 640 revolutions the BSDF (θ) drops to its minimal level (Figures 8 and 9c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Powders were placed between the concentric cylinders while the internal cylinder rotated. This system is not shown as photographs of the system have appeared in previous publications (Hernández et al, 2016;Llusa et al, 2009;Mehrotra et al, 2007). Each cylinder contains a certain number of blades controlling revolutions per minute (rpm).…”
Section: Shear Cellmentioning
confidence: 99%